1946
DOI: 10.1037/h0056873
|View full text |Cite
|
Sign up to set email alerts
|

An additional study of food aversions.

Abstract: W ALLEN has analyzed the food aversions of normal and neurotic males at a Marine training station (2), and has described a list of 20 foods which can be used in studying food dislikes (3). The following brief study utilizes this list, and the general method of the former paper, in order to provide comparable findings. PROCEDUREA neurotic group of 79 white and colored male patients from the neuropsychiatric section of the station hospital was selected. This group included 8 mild psychoneurotics, 27 moderate psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1955
1955
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…This result was taken to suggest that food novelty may be important in terms of the correlation between an individual's food-preferences and their sensation-seeking behaviour. Such findings, note, fit with earlier observations suggesting that neurotically anxious individuals tend to have a greater number of food aversions than normal ( Gough, 1946 ; Wallen, 1945 ). Otis ( 1984 , p. 743) wound-up concluding that: “In light of the relatively low correlations between the general personality measures and willingness to try new foods, this result suggest that patterns of food choice may be quite independent of general preferences and responses in other areas of life ( Rozin and Schiller, 1980 ).” Note that Otis based this conclusion on the fact that the willingness to taste unusual foods appeared largely unrelated to preferences for engaging in other kinds of novel, or risky, activity.…”
Section: Personality Traits and Their Relevance To Taste (Gustation)supporting
confidence: 90%
“…This result was taken to suggest that food novelty may be important in terms of the correlation between an individual's food-preferences and their sensation-seeking behaviour. Such findings, note, fit with earlier observations suggesting that neurotically anxious individuals tend to have a greater number of food aversions than normal ( Gough, 1946 ; Wallen, 1945 ). Otis ( 1984 , p. 743) wound-up concluding that: “In light of the relatively low correlations between the general personality measures and willingness to try new foods, this result suggest that patterns of food choice may be quite independent of general preferences and responses in other areas of life ( Rozin and Schiller, 1980 ).” Note that Otis based this conclusion on the fact that the willingness to taste unusual foods appeared largely unrelated to preferences for engaging in other kinds of novel, or risky, activity.…”
Section: Personality Traits and Their Relevance To Taste (Gustation)supporting
confidence: 90%
“…However , the means for two normal groups were 0.99 and 1.28, respectively. Gough (1946)h ad similar results with means of 5.14 and 1.23 for neurotic and normal groups respectively Smith , Powell and Ross (1955)~ -~ found a mild positive relationship between food aversions and Tay lor Manifest Anxiety scores.…”
Section: -J Snsupporting
confidence: 66%
“…Two early studies (Gough, 1946;Wallen, 1945) found food aversions to be more frequent among neurotic than among normal populations. Therefore, it was predicted that SIS scores would be inversely related to food aversion.…”
Section: Food Aversionsmentioning
confidence: 99%